Transmission efficiency of Plasmodium vivax at low parasitaemia - Thitiporn Surit; Piyarat Sripoorote; Chalermpon Kumpitak; Chayanut Suansomjit; Nongnuj Maneechai; Liwang Cui; Jetsumon Sattabongkot; Wanlapa Roobsoong; Wang Nguitragool (Malaria Journal, 2023)
Abstract Background Plasmodium vivax is responsible for much of malaria outside Africa. Although most P. vivax infections in endemic areas are asymptomatic and have low parasite densities, they are considered a potentially important source of transmission. Several studies have demonstrated that asymptomatic P. vivax carriers can transmit the parasite to mosquitoes, but the efficiency has not been well quantified. The aim of this study is to determine the relationship between parasite density and mosquito infectivity, particularly at low parasitaemia. Methods Membrane feeding assays were performed using serial dilutions of P. vivax-infected blood to define the relationship between parasitaemia and mosquito infectivity. Results The infection rate (oocyst prevalence) and intensity (oocyst load) were positively correlated with the parasite density in the blood. There was a broad case-to-case variation in parasite infectivity. The geometric mean parasite density yielding a 10% mosquito infection rate was 33 (CI 95 9–120) parasites/µl or 4 (CI 95 1–17) gametocytes/µl. The geometric mean parasite density yielding a 50% mosquito infection rate was 146 (CI 95 36–586) parasites/µl or 13 (CI 95 3–49) gametocytes/µl. Conclusion This study quantified the ability of P. vivax to infect Anopheles dirus at over a broad range of parasite densities. It provides important information about parasite infectivity at low parasitaemia common among asymptomatic P. vivax carriers.